Pharmaceutical contribution to health promotion in pharmacies and drugstores (Research, Society and Development, 2021)
Medicines have become first-rate elements and are powerful tools to alleviate human suffering, however they also produce unwanted effects, and it is necessary to evaluate the consequences of their use from this perspective. However, its irrational use has contributed to the emergence of many adverse events, with a high negative impact on the health of the population. The objective of the work was to highlight the importance of pharmaceutical services in pharmacies and drugstores. The methodology adopted for the preparation was a bibliographic review, with articles, books and dissertations in the area of ​​hematology and pharmacology, found in the electronic databases: PubMed, Scientific Electronic Library Online (SCIELO), Google Scholar, Portal USP Theses and Virtual Health Library (VHL). The pharmaceutical professional has tools such as pharmaceutical assistance, pharmaceutical care and pharmaceutical intervention that allows him to carry out his active work with society so that the patient is always the main beneficiary. The irrational use of medications is an important public health problem; therefore, it is necessary to consider the potential contribution of the pharmacist and effectively incorporate it into the health teams in order to guarantee an improvement in the use of medications.